La forma del asombro : narradoras norteamericanas contemporáneas - Cruz Yáñez, Eva ((Tierra Firme))
El libro contiene cuentos de: Leslie Marmon Silko, Anne Tyler, Jayne Anne Phillips, Cynthia Ozick, Bobbie Ann Mason, Joy Williams, Ellen Gilchrist, Rebecca Goldstein, Bharati Mukherjee, Alice Walker, Marianne Wiggins, Ann Beattie, Ursula K. Le Guin, Joyce Carol Oates y Grace Paley.